Weak guidance modal dispersion curves of an optical waveguide having a double-convex-lens cross section - Mishra V.N.; Singh V.; Prasad B.; Ojha S.P. (My University, 2025)
Using Goell's point-matching method under the weak guidance approximation, we obtain and interpret the modal dispersion curves for some low-order modes sustained by an optical waveguide whose guiding region has a double-convex-lens-like cross section. It is found that the dispersion curves are of the expected shapes. From these curves, the number of sustained modes can be obtained for known values of the size parameter, the operating frequency, and the core and cladding refractive indexes. This waveguide may be conceived as a distortion of the elliptical waveguide with a transverse compression at the major axis extremities.